The Antifibrotic Drug Halofuginone Inhibits Proliferation and Collagen Production by Human Leiomyoma and Myometrial Smooth Muscle Cells - Grudzien, Meagan M. (2009)
OBJECTIVE: To investigate the effects of the antifibrotic drug halofuginone on extracellular matrix production, cell proliferation and apoptosis of cultured myometrial and leiomyoma smooth muscle cells. DESIGN: Comparative and controlled experimental research study. SETTING: University research laboratory. PATIENTS: Leiomyoma and myometrial tissues were obtained from 8 different patients at the time of elective hysterectomy. MAIN OUTCOME MEASURES: The effects of halofuginone on cell proliferation were assessed by tritiated thymidine uptake assays and cell count assays. Effects on TGFβ1, collagen type I, and collagen type III mRNA levels were assessed by quantitative real-time PCR. Effects on apoptosis were assayed using a chemiluminescent assay to measure changes in caspase 3 and 7. RESULTS: Halofuginone inhibited cell proliferation of both leiomyoma and autologous myometrial cells in a dose-dependent manner by inhibiting DNA synthesis within 24 hrs and later inducing apoptosis (as measured by increased caspase 3/7) by 48-72 hrs. Halofuginone also significantly reduced collagen type I (α1) and collagen type III (α1) mRNA levels, as well as the profibrotic factor TGFβ1 mRNA levels in both cell types. CONCLUSIONS: These results provide evidence to support the use of the antifibrotic drug halofuginone as a novel drug treatment for uterine leiomyomas.